Binary mixtures of bent-core molecules forming distinct types of B4 phase nano- and microfilament morphologies. Issue 8 (21st June 2021) - Liu, Jiao; Shadpour, Sasan; Nemati, Ahlam; Prévôt, Marianne E.; Hegmann, Elda; Zhu, Chenhui; Hegmann, Torsten
ABSTRACT: The remarkable ability of certain molecules with a bent molecular shape to form hierarchically self-assembled helical building blocks with negative Gaussian or cylindrical curvature featuring in-layer hexatic ordering– so-called B4 phases – has quickly transformed these molecules into desirable building blocks for a variety of potential applications in optics, energy harvesting, and metamaterials. We here demonstrate that these building blocks, helical nanofilaments, helical microfilaments, and heliconical-layered nanocylinders, can to some degree be predictably blended. Supported by scanning as well as transmission electron microscopy and variable angle x-ray scattering data, the three bent-core compounds, each forming exactly one of these B4 morphologies, in binary mixtures at a 1:1 molar ratio, form either the third missing, or one of the two but with opposite handedness, or a random mixture of the two selected morphologies with larger overall dimensions. Furthermore, for two of the mixtures the a priori predicted handedness of the chiral filaments was experimentally confirmed. The third mixture with a priori predicted antagonistic handedness of the initial morphologies forms a combination of the two, one apparently achiral and the other one with opposite handedness. GRAPHICAL ABSTRACT: uf0001